Komitmen Penyuluhan Pertanian Pada Tanaman Padi Organik di Dinas Pertanian Kabupaten Bandung (Studi Kasus di Kabupaten Ciparay) - Hidayat; Tita Meirina Djuwita; Yani Hendrayani (Asosiasi Ahli Administrasi Indonesia, 2020)
The commitment of agricultural extension to organic rice crops (oryza sativa) in Ciparay sub-district still has not contributed to the development /progress of organic rice farmers. This research is intended to know and analyze information about the situation and conditions about the effect of agricultural extension commitment on organic rice crops (oryza sativa) in the Agriculture Services Bandung Regency. This research method used a qualitative approach with descriptive analysis methods because they wanted to clearly describe and interpret the data or symptoms obtained during the research. The data collection techniques in this research used observations, interviews, library studies and other data sources that support the research. The results showed that the commitment of agricultural extension to organic rice crops (oryza sativa) in Agriculture Services Bandung Regency is quite high despite some constraints, this is due to factors that have not been optimal to effectiveness, both in terms of ability to adjust, job satisfaction and resource achievement. The success of organic rice farming can be seen from the high commitment aspect of the implementation of organic cultivation counseling in rice fields, namely: continuous commitment, understanding, feeling and obeying the regulations of the implementation of counseling programs, communication and implementation precisely on targets and objectives as corrective action materials in order to minimize the irregularities that will occur in future extension programs.